2020
DOI: 10.3389/fphar.2020.01061
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Ferroptosis and Applications in Tumor Treatment

Abstract: Iron-dependent ferroptosis is a new form of cell death in recent years, which is driven by lipid peroxidation. The lethal lipid accumulation caused by glutathione depletion or inactivation of glutathione peroxidase 4 (GPX4) is characteristic of the ferroptosis process. In recent years, with the in-depth study of ferroptosis, various types of diseases have been reported to be related to ferroptosis. In other words, ferroptosis, which has attracted widespread attention in the fields of biochemistry, oncology, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 117 publications
0
66
0
Order By: Relevance
“…Ferroptosis is a newly discovered form of cell death, which is characterized by the iron-dependent accumulation of lipid reactive oxygen species (ROS). 6 Emerged reports reveal that cancer treatment options based on the induction of ferroptosis effectively eliminate the number of cancer cells. Sorafenib, which induces the induction of ferroptosis, has been approved by the FDA to treat hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferroptosis is a newly discovered form of cell death, which is characterized by the iron-dependent accumulation of lipid reactive oxygen species (ROS). 6 Emerged reports reveal that cancer treatment options based on the induction of ferroptosis effectively eliminate the number of cancer cells. Sorafenib, which induces the induction of ferroptosis, has been approved by the FDA to treat hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis is a recently discovered unique form of programmed cell death driven by mitochondrial lipid peroxidation and dysregulation of cellular iron metabolism. 6 Unlike necroptosis or apoptosis, ferroptosis is independent of receptor-interacting protein 1 (RIPK1) kinase activity and caspase activity. 7 With the in-depth study, multiple lines have indicated that ferroptosis is related to various types of diseases, especially carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific induction of ferroptosis in tumor cells has become a novel target for tumor therapy. Ferroptosis induced by small molecular compounds can evade chemotherapeutic drug resistance and induce the death of cancer cells under the condition that some classical chemotherapeutic drugs have no effects [ 4 ]. The application of nanobiology technology in the efficient delivery of antitumor drugs conforms to the biological characteristics of tumors to a certain extent with great advantages in the efficiency of drug delivery.…”
Section: Tumor Therapy Based On Nonepigenetic and Epigenetic Of Fementioning
confidence: 99%
“…Ferroptosis is an important form of RCD, caused by the accumulation of lipid free radicals dependent on iron ions, and is lucubrated more extensively in the mechanism of cancer treatment [ 3 ]. Ferroptosis is involved in the occurrence and evolution of a variety of diseases, such as tumor [ 4 ], ischemia reperfusion injury (IRI) [ 5 ], renal failure [ 6 ], neurological diseases [ 7 ], and hematological diseases [ 8 ]. Especially in cancer research, ferroptosis can induce the death of various tumor cells, including in liver cancer, pancreatic cancer, and breast cancer, but its mechanism remains to be further explored [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%